Increased exhaled nitric oxide precedes lung fibrosis in two murine models of systemic sclerosis. (16th June 2015) - Hua-Huy, Thong; Le-Dong, Nhat-Nam; Duong-Quy, Sy; Bei, Yihua; Rivière, Sébastien; Tiev, Kiet-Phong; Nicco, Carole; Chéreau, Christiane; Batteux, Frédéric; Dinh-Xuan, Anh Tuan
Abstract: Exhaled nitric oxide (NO) is increased as a result of lung inflammation, which in turn causes subsequent interstitial lung disease in patients with systemic sclerosis (SSc). However, the exact time course of inflammatory and fibrotic changes in the SSc lung has not yet been described. Our objective was to assess the chronological evolution of lung inflammatory and fibrotic processes in mice pre-treated with hypochlorous acid (HOCl) or bleomycin. C57BL/6 mice were randomized into three groups receiving subcutaneous injections of HOCl, bleomycin, or PBS for 2, 4 or 6 weeks. Exhaled NO (eNO) was measured at the end of each injection period and after 2 resting weeks without injection (8 week group). Mice were then sacrificed to obtain skin and lung tissues to measure fibrotic changes and NO synthases (NOS) expression. Increased eNO, inducible NOS and nitrotyrosine expression in bronchial epithelium, lung neutrophils and macrophages were observed at early phases in both HOCl- and bleomycin-treated mice. Conversely, lung vascular endothelial NOS expression decreased significantly at 6th and 8th weeks. Skin fibrosis was significantly increased from the 4th week and lung fibrosis from 6th week. We conclude that lung inflammation occurs early after injury as reflected by increased exhaled NO and inducible NOS expression, and precedes fibrotic changes in skin and lungs of mice pre-treated with bleomycin and HOCl. Early detection and treatment of pulmonary inflammation might be useful in preventing subsequent occurrence of lung fibrosis in SSc patients.